Label-Free Imaging of Umbilical Cord Tissue Morphology and Explant-Derived Cells - Raf Donders (Stem Cells International, 2016)
In situ detection of MSCs remains difficult and warrants additional methods to aid with their characterization in vivo. Two-photon confocal laser scanning microscopy (TPM) and second harmonic generation (SHG) could fill this gap. Both techniques enable the detection of cells and extracellular structures, based on intrinsic properties of the specific tissue and intracellular molecules under optical irradiation. TPM imaging and SHG imaging have been used for label-free monitoring of stem cells differentiation, assessment of their behavior in biocompatible scaffolds, and even cell tracking in vivo. In this study, we show that TPM and SHG can accurately depict the umbilical cord architecture and visualize individual cells both in situ and during culture initiation, without the use of exogenously applied labels. In combination with nuclear DNA staining, we observed a variance in fluorescent intensity in the vessel walls. In addition, antibody staining showed differences in Oct4, αSMA, vimentin, and ALDH1A1 expression in situ, indicating functional differences among the umbilical cord cell populations. In future research, marker-free imaging can be of great added value to the current antigen-based staining methods for describing tissue structures and for the identification of progenitor cells in their tissue of origin.